EFL Learners’ Stories in Essay Writing: A Narrative Analysis - Rifai, Irfan; Nurbani, Armelia Nungki; Bachtra, Julian (PANYONARA: Journal of English Education, 2024)
This qualitative research is aiming at exploring EFL learners’ stories when writing an essay. To be specific, this research is centered on examining the problems faced by EFL learners when writing essays and their strategies to overcome the problems. Six EFL university students from the third to eighth semesters of the English department at one of private universities in Surabaya participated in the research. The participants were selected based on their ability that is categorized as lower and higher achievers, gender and level of study/semester. The data were generated by interviewing the participants and analyzing their documents work. The data obtained from interviews were transcribed verbatim and analyzed using content analysis, while the data from the students’ tasks are classified based on the errors. The later data are used to cross check the data obtained from interviews. The data analysis showed that finding, translating, and realizing suitable ideas into writing and using appropriate tenses and modals grammar were prominent problems of EFL learners. In addition, difficulty to organize paragraphs cohesively and coherently are also noticeable problems. The research results also indicated that the learners were aware of the challenges in writing essays, therefore, they creatively seek strategies to tackle the problems by watching YouTube, TV, news, and reading articles and English books.